Geospatial perspectives on health: The PrEP4Love campaign and the role of local context in health promotion messaging. (November 2020) - Phillips II, Gregory; McCuskey, David J.; Felt, Dylan; Raman, Anand B.; Hayford, Christina S.; Pickett, Jim; Shenkman, Julia; Lindeman, Peter T.; Mustanski, Brian
Abstract: Pre-exposure prophylaxis (PrEP) remains one of the most effective biomedical interventions for the prevention of HIV transmission. However, uptake among populations most impacted by the HIV epidemic remains low. La rge-scale awareness and mobilization campaigns have sought to address gaps in knowledge and motivation in order to improve PrEP diffusion. Such campaigns must be cognizant of the historical, physical, and structural contexts in which they exist. In urban contexts, neighborhood segregation has the potential to impact health outcomes and amplify disparities. Therefore, we present novel geospatial approaches to the evaluation of a Chicago-based PrEP messaging campaign (PrEP4Love) in a 2018 cohort of men who have sex with men and transgender women, contextualizing results within the localized infrastructure and public health landscape, and examining associations between geographic location and campaign efficacy. Results revealed notable variance in rates of PrEP uptake associated with campaign exposure by Chicago planning area, which are likely explained by the historical and contemporary impacts of racist structures on physical environment and city infrastructure. Findings have important implications for the evaluation and implementation of future messaging campaigns, which should take the unique historical, structural, and geospatial factors of their particular settings into account in order to achieve maximum impact. Highlights: Health messaging campaigns should consider geospatial contexts. City infrastructure and services may influence the distribution of advertisements. Historical, structural discrimination results in inequitable message diffusion. It is vital to consider how these structures will impact campaign efficacy. Service and transportation access are key components in PrEP messaging strategies.